Psycho-Social Correlates of Loneliness among Adolescents – A Study in the City Chandigarh: Examining the psycho-social aspects of loneliness among adolescents in Chandigarh (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Social relationships are at the core of human life. Satisfying social relationships are vital for good mental and physical health. As humans we possess a need to belong, which constitutes a fundamental motivation – driving our thoughts, emotions and interpersonal behaviour. This need to belong comprises a pervasive desire to form and maintain atleast a minimum quantity of lasting positive and significant interpersonal relationships. The phenomenon of loneliness is difficult to define, yet it is one of most important dimensions of human behavior. To date, the experts have not agreed upon a definition. Further, there are neither defined theoretical frameworks which explain loneliness nor is there any consensus regarding the causes and consequences. In the present paper an attempt has been made to study the Psycho-social correlates of Loneliness among adolescents in Chandigarh. In view of high prevalence of loneliness among adolescents the study identified the psychological predictors of loneliness by including in its purview depression, hopelessness, negative automatic thoughts, social support (quantitative), social support (qualitative), ten dimensions of family environment, five dimensions of Cattell’s second-order anxiety factor, and locus of control.